Effect of Cypermethrin on the Growth of Ciliate Protozoan Paramecium caudatum - Dutta, Joydeep (Toxicol Int, 2015)
OBJECTIVE: The objective of this study is to assess the effect of cypermethrin on the growth of ciliate protozoan Paramecium caudatum. MATERIALS AND METHODS: Monoxenic culture of P. caudatum, were exposed to different doses (0.01, 0.05, 0.1, 0.15, and 0.2 µg/L) of cypermethrin along with control for 24, 48, 72, and 96 h time interval. The total numbers of live and dead cells were counted after trypan blue staining in Neubauer hemocytometer. RESULTS: Marked decrease in the number of living cells with the increase in the concentration of cypermethrin and with increasing exposure time intervals was recorded. CONCLUSION: The results indicate that cypermethrin is toxic to P. caudatum even at low concentrations when it enters in the aquatic system through runoff.